2004
DOI: 10.1210/en.2003-1620
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor and Its Receptor, Flk-1/KDR, Are Cytoprotective in the Extravascular Compartment of the Ovarian Follicle

Abstract: Vascular endothelial growth factor (VEGF) is a potent mitogen and cytoprotective factor for vascular endothelial cells. Although VEGF is ubiquitously expressed, its role in nonvascular tissues is poorly understood. VEGF interacts with various cell surface receptors to mediate its cellular effects. It previously has been thought that the VEGF receptor Flk-1/KDR, its main signaling receptor, was expressed exclusively by endothelial cells. However, in the present study using bovine and rodent models, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
117
0
10

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 63 publications
12
117
0
10
Order By: Relevance
“…An increasing number of reports suggest that VEGFA has direct effects on nonvascular cells including neuronal cells (Marti & Risau 1998, Wada et al 2006, Nishijima et al 2007), muscle cells (Germani et al 2003, Bryan et al 2008, and granulosa cells (Greenaway et al 2004). Data also suggest potential functional roles for VEGFA in the postnatal testis, as KDR and FLT1 are expressed in testicular germ cells in humans (Ergun et al 1997), rats (Rudolfsson et al 2004), and mice (Nalbandian et al 2003), while somatic Sertoli and Leydig cells produce VEGFA (Liu & Yang 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of reports suggest that VEGFA has direct effects on nonvascular cells including neuronal cells (Marti & Risau 1998, Wada et al 2006, Nishijima et al 2007), muscle cells (Germani et al 2003, Bryan et al 2008, and granulosa cells (Greenaway et al 2004). Data also suggest potential functional roles for VEGFA in the postnatal testis, as KDR and FLT1 are expressed in testicular germ cells in humans (Ergun et al 1997), rats (Rudolfsson et al 2004), and mice (Nalbandian et al 2003), while somatic Sertoli and Leydig cells produce VEGFA (Liu & Yang 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This method provides a novel tool to study the function of VEGFA and its receptors and apoptosis genes of MGC in vitro. Previous reports have indicated that VEGF and its receptors, VEGFR-1 and VEGFR-2, are expressed in pig follicle cells (Barboni et al, 2000), bovine granulosa cells (Einspanier et al, 2002;Greenaway et al, 2004) and MGC (Wulff et al, 2002) in a coordinated fashion in which they protect these cells from apoptosis, which demonstrates that VEGF functions as a survival factor for ovarian follicle and granulosa cells (Kosaka et al, 2007). Therefore, the inhibition of the VEGF gene by RNAi strategy to study its function in MGC requires an understanding of the related effects of this strategy downstream of the VEGF-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike VEGF, which is produced by most cell types, research has previously demonstrated that the VEGF receptors Flt-1 and Flk-1 are coexpressed in vascular cells (Ferrara, 2002) including granulosa cells in which they interact to protect these cells against apoptotic cell death, and inhibition of VEGF causes a decrease in Flt and Flk expression (Greenaway et al, 2004;Kosaka et al, 2007). Flt-1 is believed to be expressed in ovarian follicles that consist of oocyte, granulosa cells and the cells of the internal and external theca layer (Okamura et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations